2008
DOI: 10.2478/v10057-008-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of comprehension of ironic utterances in 3- to 9-year-old Finnish-speaking children

Abstract: This study explores the comprehension of simple ironic utterances in 210 Finnish children aged from 3 to 9 years. If the child answered the question correctly, he/she was asked to explain correct answers. The results indicated that there was large individual variation within age groups both in answers and explanations. In terms of correct answers there was a significant difference between 6-and 7-year-olds and in correct explanations between age groups of 3-4, 6-7 and 7-8. Analysis of incorrect answers showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
5
25
0
3
Order By: Relevance
“…Studies have shown that at around 5 or 6 years of age typically developing children begin to understand or detect that the ironic speaker means something very different (often the opposite) to what they have literally said (Hancock et al 2000;Harris and Pexman 2003;Keenan and Quigley 1999;Nakassis and Snedeker 2002;Winner and Leekam 1991). There is some evidence for comprehension at younger ages (Loukusa and Leinonen 2008;Recchia et al 2010), especially if the irony references failed expectations that can be directly perceived (Angeleri and Airenti 2014). Children's understanding of the ironic speaker's intent or purpose seems to emerge somewhat later, around age 7 or 8 (Ackerman 1983;Andrews et al 1986;Hancock et al 2000;Loukusa and Leinonen 2008).…”
Section: Pragmatic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that at around 5 or 6 years of age typically developing children begin to understand or detect that the ironic speaker means something very different (often the opposite) to what they have literally said (Hancock et al 2000;Harris and Pexman 2003;Keenan and Quigley 1999;Nakassis and Snedeker 2002;Winner and Leekam 1991). There is some evidence for comprehension at younger ages (Loukusa and Leinonen 2008;Recchia et al 2010), especially if the irony references failed expectations that can be directly perceived (Angeleri and Airenti 2014). Children's understanding of the ironic speaker's intent or purpose seems to emerge somewhat later, around age 7 or 8 (Ackerman 1983;Andrews et al 1986;Hancock et al 2000;Loukusa and Leinonen 2008).…”
Section: Pragmatic Developmentmentioning
confidence: 99%
“…There is some evidence for comprehension at younger ages (Loukusa and Leinonen 2008;Recchia et al 2010), especially if the irony references failed expectations that can be directly perceived (Angeleri and Airenti 2014). Children's understanding of the ironic speaker's intent or purpose seems to emerge somewhat later, around age 7 or 8 (Ackerman 1983;Andrews et al 1986;Hancock et al 2000;Loukusa and Leinonen 2008). Children's appreciation tends to be more accurate for more direct forms of verbal irony: ironic criticisms like "you are so graceful" rather than the less direct "you could be an acrobat" (Dews et al 1996;Hancock et al 2000;Harris and Pexman 2003;Pexman et al 2005).…”
Section: Pragmatic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Empiezan a entender que hay enunciados con los que el hablante no quiere dar a entender lo que dice literalmente sino que se propone transmitir algo más que el sentido literal de sus palabras (Creusere, 2000;Loukusa & Leinonen, 2008;Nilsen, Glenwright & Huyder, 2011; Nippold, 2007). No obstante, los niños de esta edad, e incluso algunos un poco mayores (8-9 años), suelen interpretar las expresiones irónicas como errores del hablante o mentiras, dado que basan sus juicios más en rasgos de la personalidad, rostro y cuerpo del hablante que en la expresión irónica en sí (Andrews, Rosenblatt, Malkus, Gardner & Winner, 1986;Bosco, Angeleri, Colle, Sacco & Bara, 2013;Dews et al, 1996;Nilsen, Glenwright & Huyder, 2011;Pexman, Glenwright, Hala, Kowbel & Jungen, 2006).…”
Section: La Ironía Verbal En El Desarrollo Lingüístico Tardíounclassified
“…En términos generales, los resultados del estudio indican que desde los 9 años los niños son capaces de interpretar textos con final no-irónico como tales, mientras que la capacidad para interpretar aquellos con final irónico aumenta de manera significativa entre los 12 y los 15 años. Lo anterior confirma que el desarrollo de la interpretación de las expresiones irónicas va más allá de la infancia temprana, como ya ha sido seña-lado previamente por otros investigadores (Andrews et al, 1986;Burnett, 2014;Creusere, 2000;Loukusa & Leinonen, 2008;Nilsen, Glenwright & Huyder, 2011;Pexman & Glenwright, 2007;Pexman et al, 2005;Winner & Leekam, 1991). Por otra parte, los resultados del estudio también señalan que, de manera general, la presencia de pistas lingüísticas en las expresiones irónicas favorece la interpretación de la ironía verbal, sobre todo en los individuos de 9 y 12 años, pero que las pistas no necesariamente incrementan las reflexiones que los individuos son capaces de hacer cuando se les pide que proporcionen las razones por las que consideran que cierta expresión es irónica.…”
Section: Discusión Y Conclusionesunclassified